2020
DOI: 10.1186/s12876-020-01422-9
|View full text |Cite
|
Sign up to set email alerts
|

Very low risk of lymph node metastasis in Epstein-Barr virus-associated early gastric carcinoma with lymphoid stroma

Abstract: Background: Epstein-Barr virus-associated early gastric carcinoma with lymphoid stroma (EBV-GCLS) is a rare variant of early gastric carcinomas. Clinicopathological features of this variant remain obscure, especially in Chinese patients. Therefore, we collected EBV-GCLS cases and studied clinicopathology and prognosis. Methods: By a retrospective review of 595 consecutive radical gastrectomies for early gastric carcinoma from 2006 to 2018, we identified 8 (1.3%, 8/595) EBV-GCLS cases. Clinicopathologic charact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
(71 reference statements)
1
6
0
Order By: Relevance
“…Programmed cell death (PD)-1/PD-L1 immunotherapy has been widely approved for treatment of lung cancer, liver cancer and other malignant tumors[ 12 ] but there are few reports on GCLS. PD-1/PD-L1 are known to be highly expressed in GCLS, often at higher rates than in gastric adenocarcinoma[ 13 ]. The TCGA study identified some characteristics to suggest that EBV tumors are potential candidates for immunotherapy with PD-1/PD-L1 pathway inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Programmed cell death (PD)-1/PD-L1 immunotherapy has been widely approved for treatment of lung cancer, liver cancer and other malignant tumors[ 12 ] but there are few reports on GCLS. PD-1/PD-L1 are known to be highly expressed in GCLS, often at higher rates than in gastric adenocarcinoma[ 13 ]. The TCGA study identified some characteristics to suggest that EBV tumors are potential candidates for immunotherapy with PD-1/PD-L1 pathway inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of nodal metastasis is lower in EBV-positive GCs than in EBV-negative GCs [ 1 , 17 , 18 ]; however, for deeply invasive GCs, the frequency of lymph node metastasis is fairly high, even in EBV-positive GCs [ 17 ]. In the present case, the EBV-positive component invaded up to the serosa, while the EBV-negative component invaded up to the subserosa; only the EBV-positive component involved the lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…EBVaGC is regularly removed by surgical resection since it is an undifferentiated-type cancer. Early EBVaGC has a low risk of lymph node metastasis [ 123 ]. A study presented that EBV-associated GC has a significantly low incidence of lymph node metastasis and a better prognosis compared with EBV-negative GC.…”
Section: Epstein-barr Virus (Ebv)mentioning
confidence: 99%